Age-dependent modulation of vascular niches for haematopoietic stem cells - Kusumbe, Anjali P.; Ramasamy, Saravana K.; Itkin, Tomer; Mäe, Maarja Andaloussi; Langen, Urs H.; Betsholtz, Christer; Lapidot, Tsvee; Adams, Ralf H. (Nature (London), 2016)
Notch signalling in endothelial cells of the bone induces change in the capillaries and mesenchymal stem cells of the environment to support haematopoietic stem cell amplification. Age-linked changes in bone marrow Blood vessels in the bone marrow provide signals to the haematopoietic stem cells, however, how these signals modulate haematopoietic stem cell (HSC) function and change as an organism age is unclear. Ralf Adams and colleagues used imaging and cell-type-specific genetic mouse models to investigate the nature of vascular niches for HSCs in bone. They find that Notch signalling in bone endothelial cells induces change in the capillaries and mesenchymal stem cells of the environment to support HSC amplification. These signals are reduced in aged organisms, but activation of Notch can restore some of these properties. Elsewhere in this issue ( page 323 ), Tomer Itkin et al . show that the different functions of bone marrow endothelial cells are regulated by distinct types of endothelial blood vessels with different permeability properties, affecting levels of reactive oxygen species in their neighbouring stem cells. Blood vessels define local microenvironments in the skeletal system, play crucial roles in osteogenesis and provide niches for haematopoietic stem cells 1 , 2 , 3 , 4 , 5 , 6 . The properties of niche-forming vessels and their changes in the ageing organism remain incompletely understood. Here we show that Notch signalling in endothelial cells leads to the expansion of haematopoietic stem cell niches in bone, which involves increases in CD31-positive capillaries and platelet-derived growth factor receptor-β (PDGFRβ)-positive perivascular cells, arteriole formation and elevated levels of cellular stem cell factor. Although endothelial hypoxia-inducible factor signalling promotes some of these changes, it fails to enhance vascular niche function because of a lack of arterialization and expansion of PDGFRβ-positive cells. In ageing mice, niche-forming vessels in the skeletal system are strongly reduced but can be restored by activation of endothelial Notch signalling. These findings indicate that vascular niches for haematopoietic stem cells are part of complex, age-dependent microenvironments involving multiple cell populations and vessel subtypes.